Capsazepine concentration dependently inhibits currents in HEK 293 cells mediated by human hyperpolarization-activated cyclic nucleotide-gated 2 and 4 channels. (September 2013) - Zuo, Guang-Feng; Li, Ming-Hui; Zhang, Jun-Xia; Li, Bing; Wang, Zhi-Mei; Wang, Qiang; Xiao, Hang; Chen, Shao-Liang
Recent studies indicate that blockade of currents (Ih ) mediated by hyperpolarization-activated cyclic nucleotide-gated (HCN) channels (particularly HCN1) may partly account for the antinociceptive effects of capsazepine (CPZ). Unfortunately, determining whether capsazepine is a selective HCN channel blocker and determining its adverse effects when it is used for the treatment of neuropathic pain, have been thus far understudied. In this study, we aimed to elucidate the effects of capsazepine on human HCN2 (hHCN2) and HCN4 (hHCN4) channels in HEK293 cells. The vectors that expressed hHCN2 and hHCN4 cDNA were constructed and transfected into HEK293 cells. Enhanced green fluorescent protein (EGFP) fluorescence and the reverse transcription polymerase chain reaction (RT-PCR) were used to confirm the successful transfection of the vectors. After G418 (neomycin) screening, cell lines that expressed hHCN2 and hHCN4 were obtained. The whole-cell voltage-clamp technique was used to determine the currents from hHCN2 and hHCN4 channels, which were perfused with five concentrations (0.1 µM, 1 µM, 5 µM, 10 µM and 50 µM) of capsazepine. The results showed that capsazepine at the range from 0.1 to 50 µM markedly inhibited hHCN2 and hHCN4 currents in a concentration-dependent manner, with most inhibition achieved at a concentration of 10 µM of capsazepine. When compared with the control group, a V0.5 for the hHCN2 and hHCN4 channel showed that 10 µM capsazepine significantly shifted the membrane potential towards hyperpolarization. The present results indicate that capsazepine is not a selective HCN1 channel blocker and that it may have adverse effects when used to treat neuropathic pain.